Pressure-induced irreversible amorphization and metallization with a structural phase transition in arsenic telluride. Issue 46 (20th November 2017) - Dai, Lidong; Zhuang, Yukai; Li, Heping; Wu, Lei; Hu, Haiying; Liu, Kaixiang; Yang, Linfei; Pu, Chang
Abstract : A crystalline to amorphous and metallic transition was demonstrated by impedance spectroscopy, Raman spectroscopy, AFM and HRTEM in DAC. Abstract : The structural, vibrational and electronic properties of α-As2 Te3 in different pressure environments were investigated using a diamond-anvil cell (DAC) in conjunction with AC impedance spectroscopy, Raman spectroscopy, atomic force microscopy and high-resolution transmission electron microscopy up to ∼25 GPa. Under non-hydrostatic conditions, α-As2 Te3 endured a structural phase transition at ∼6 GPa, and a ∼2 GPa delay in the transition point was observed under hydrostatic conditions. With increasing pressure, amorphization and metallization simultaneously appeared at ∼11 GPa, as characterized by the Raman spectra and temperature-dependent conductivity results. We found that both amorphization and metallization were irreversible after decompression under non-hydrostatic conditions. However, under hydrostatic conditions, both amorphization and metallization were reversible. The unique properties displayed by α-As2 Te3 in different pressure environments may be attributed to the effects of deviatoric stresses and the interlayer interaction constrained by the pressure medium.